2014
DOI: 10.1007/s00467-014-2772-0
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of intravenous hydralazine for the treatment of hypertension in the hospitalized child

Abstract: In hospitalized children, IV hydralazine was well tolerated, BP response was variable, and 21 % of the patients achieved a ≥25 % reduction of systolic or diastolic BP. Further studies are needed to compare the safety and efficacy of IV hydralazine to other short-acting antihypertensive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…An average reduction in MAP of 19% was observed and a clinical response, defined as 10%–25% reduction in MAP, was demonstrated in 47% of patients. Similar to the aforementioned results by Ostrye et al, 33 a substantial number of patients (31%) demonstrated a potentially excessive BP drop, defined as >25% MAP reduction. 34 …”
Section: Medicationssupporting
confidence: 85%
See 2 more Smart Citations
“…An average reduction in MAP of 19% was observed and a clinical response, defined as 10%–25% reduction in MAP, was demonstrated in 47% of patients. Similar to the aforementioned results by Ostrye et al, 33 a substantial number of patients (31%) demonstrated a potentially excessive BP drop, defined as >25% MAP reduction. 34 …”
Section: Medicationssupporting
confidence: 85%
“…That being said, results from two recent single-center retrospective studies evaluating the efficacy and safety of IV hydralazine in hospitalized children are now available. In 110 hospitalized children, Ostrye et al 33 reported a median reduction in systolic and diastolic BP of 8.5% and 11.5%, respectively. Of some concern, 21% of patients studied achieved a BP reduction exceeding 25% and an increase in BP was observed in 30% of the patients.…”
Section: Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of intravenous hydralazine in children in with acute HTN has been found safe and effective; however, the change in BP has been variable. In addition, primary adverse effects reported include rebound tachycardia, edema, and excessive BP reduction [134]. In addition, although the risk is higher in adults, hydralazine has the potential of inducing or exacerbating systemic lupus erythematosus in 5-10% of patients [135].…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…To address HTN among hospitalized children, “as‐needed” (PRN) antihypertensives are commonplace in inpatient care 9,10‐15 . However, recognition of abnormal BP in hospitalized children can be hindered by the need to consult age, sex, and height‐based BP percentiles for children <13 years of age; distractions and heavy clinical demands; the asymptomatic nature of hypertensive urgency; and non‐specific symptoms of hypertensive emergency in younger, especially non‐verbal, children.…”
Section: Introductionmentioning
confidence: 99%